Weighted Differentiation Composition Operator from Logarithmic Bloch Spaces to Zygmund-Type Spaces - Huiying Qu; Yongmin Liu; Shulei Cheng (Abstract and Applied Analysis)
Let H(𝔻) denote the space of all holomorphic functions on the unit disk 𝔻 of ℂ, u∈H(𝔻) and let  n be a positive integer, φ a holomorphic self-map of 𝔻, and μ a weight. In this paper, we investigate the boundedness and compactness of a weighted differentiation composition operator 𝒟φ,unf(z)=u(z)f(n)(φ(z)),f∈H(𝔻), from the logarithmic Bloch spaces to the Zygmund-type spaces.